Hospitalidade e percepção de qualidade em processos de atendimento ao cliente: um estudo em instituições de ensino superior - OLIVEIRA, Luciane Santos de (2018)
Extraclass issues in Higher Education Institutions (HEIs) have not received the attention which it is importance suggests. Education is a service and, as such, the service provided to the students should be considered as a factor of evaluation of quality and loyalty, avoiding the school evasion rates. The research of hospitality in service management plays a fundamental role in analysis of the quality of relations established in this context. The services sector presents a mix of tangible and intangible factors, however, the study of the hospitality in this scenario propitiates to establish what prevails in the perception of quality in services, these being the intangible factors. The present dissertation aimed to analyze the relationship between hospitality and provision of services in higher education institutions under the satisfaction of the student. The question that guides the research is: how to hospitality and service infrastructure in the service process influence the perception of student satisfaction in HEI? The specific objectives are: to identify if hospitality is positively recognized by students; to if the identify infrastructure of services is a criterion of satisfaction; compare the two evaluations. The hypotheses proposed were: H1 - The service infrastructure positively influences the evaluation of students about the HEIs; and H2 - Hospitality positively influences students' evaluation of the HEIs. The methodological and technical procedures started from a literature review about Hospitality, Services, Service Management and HEI for the purpose of evidence variables for subsequent application in a survey among students of three HEIs through a questionnaire structured on a 7-point Likert scale. The main results were: service infrastructure is less relevant if compared to the influence that the hospitality inserts on the perception of quality in services in the educational sector, where hospitality it is being the factor that has the greatest impact on student satisfaction.